Stilistika dalam Dwilogi Novel Rahvayana Karya Sujiwo Tejo dan Pemanfaatannya sebagai Alternatif Materi Pembelajaran Apresiasi Sastra di SMA: Stylistics In The Dwilogy Of Rahvayana's Novel Sujiwo Tejo and Its Utilization as Alternative Literature Appreciation Learning Materials at Senior High School - Ilham Adi Setiawan (TOTOBUANG, 2022)
This research describes the style of Sujiwo Tejo in the Dwilogy of the novel Rahvayana. The stile phenomenon used by Sujiwo Tejo in the Dwilogy of the novel Rahayana creates special effects and becomes an attraction for further study. The Sujiwo Tejo style was studied using a genetic stylistic approach. In addition, stylistics has a specialty used to reveal the author's ideology from the language he conducts. The purpose of this research studies the elements of action, such as the figure of the speech and imagery; the content or ideology of the author, such as biography, socio-historical author, and the sociocultural conditions of the community when it had written; the use of research results as an alternative learning material for appreciation literature in high school. This descriptive research uses a design of the genetic stylistic approach. The data in this study are the quotes from the Rahvayana Dwilogy, various references related to the ideology of Sujiwo Tejo, and the syllabus of the seventh class of the high school. The data analysis technique used is the genetic stylistic analysis technique. The result indicates (1) the dictions are dominantly vulgar and the absorption words as a means to convey various expressions; (2) the figure of speech used by Sujiwo Tejo in the Dwilogy in the novel Rahvayana dominantly uses comparison and contrast, (3) the figure of speech used by Sujiwo Tejo to create an aesthetic effect; (4) the imagery used by Sujiwo Tejo in the Dwilogy of the novel Rahvayana is dominant with intellectual imagery; (5) The ideology of Sujiwo Tejo in the Dwilogy of the novel Rahvayana which viewed from the biographical, socio-historical, and sociocultural conditions of the community reflects the ideology of siding with the character Ravana. Keywords: style, genetic stylistics, Dwilogy of  Rahvayana novel, ideology